Dental aberrations: A short review - Souparna Madhavan; B Haifa (Wolters Kluwer Medknow Publications, 2021)
Oral health-care services provided by the dentist have to follow certain standards to avoid any kind of negligence during treatment. Patient safety is an important aspect of quality in health care system. In the present time, all dentists need to be cautious about the general perception and the high cost involved in the treatment and to avoid any serious injury to the patient. The best way to prevent being involved in a litigation is to follow a good clinical practice patterns. This article emphasizes on common clinical mishap and dental patient incidents in a clinical practice.